Anti-oxidative effects of ascorbic acid on buffalo erythrocytes in vitro - SINGH, V; JAIN, V K; KUMAR, RAKESH; ., SRIDHAR (The Indian Journal of Animal Sciences, 2011)
The present investigation was undertaken to assess the anti-oxidative effects of ascorbic acid on erythrocytic oxidative stress in buffaloes in vitro. Buffalo plasma was first rendered deficient in inorganic phosphorus and then buffalo erythrocytes were resuspended in this Pi deficient plasma and finally treated with acetylphenylhydrazine, a known oxidizing agent, in vitro. These resuspended erythrocytes under oxidative stress condition were subjected to ascorbic acid treatment. There was significant decrease in erythrocytic oxidative stress as revealed by significant decrease in erythrocytic Heinz bodies, level of malondialdehyde and erythrocytic osmotic fragility following ascorbic acid treatment in vitro.Â